2018
DOI: 10.2478/jim-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Intima-media Thickness, Risk Factors, and Markers of Inflammation in Cardiovascular Disease

Abstract: Introduction:The burden of coronary artery disease (CAD) and peripheral vascular pathologies caused by atherosclerosis is constantly increasing. There is continuous research aiming to develop new methods that can evaluate the extent of atherosclerotic disease in different vascular beds, thus estimating global risk. Similar to carotid artery thickness, which is an established marker for increased cardiovascular risk and cerebrovascular disease, femoral intima-media thickness (f-IMT) may have the same role in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
2
0
2
Order By: Relevance
“…4 Common femoral arteries lay shallowly to the superficial surface and appear to be easy to evaluate morphology and size, recently, studies started focusing on the potential role of intima-media thickness measured at the femoral artery in assessing cardiovascular risk and increased IMT at the femoral arteries in a population suffering from hypertensive and diabetes patients. [5][6][7] Intima-media thickness under 2D ultrasound findings is one of the useful surrogate endpoints for arterial diseases and a feasible method in routine clinical practice. 8,9 Doppler ultrasonography is a practical method to discover and measure arterial media as well as sizes of atherosclerosis plaques, blood flow velocity, which results in a good screening apparatus to evaluate and to prognosis arterial thrombosis and occlusion with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…4 Common femoral arteries lay shallowly to the superficial surface and appear to be easy to evaluate morphology and size, recently, studies started focusing on the potential role of intima-media thickness measured at the femoral artery in assessing cardiovascular risk and increased IMT at the femoral arteries in a population suffering from hypertensive and diabetes patients. [5][6][7] Intima-media thickness under 2D ultrasound findings is one of the useful surrogate endpoints for arterial diseases and a feasible method in routine clinical practice. 8,9 Doppler ultrasonography is a practical method to discover and measure arterial media as well as sizes of atherosclerosis plaques, blood flow velocity, which results in a good screening apparatus to evaluate and to prognosis arterial thrombosis and occlusion with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Yang mana semakin tebal IMT arteri femoralis semakin berat stenosis arteri koronaria. Hal ini sesuai dengan literatur bahwa ketebalan tunika intima-media merupakan penanda risiko aterosklerosis arteri koronaria 6,7,14 juga membuktikan bahwa keadaan dinding arteri femoralis mencerminkan keadaan dinding arteri koroner, sehingga penebalan FIMT dapat dipakai sebagai penanda terdapatnya aterosklerosis pada pembuluh darah jantung. Penelitian sebelumnya mengatakan aerosklerosis berkembang lebih lambat di SFA dibandingkan dengan arteri koroner dan karotis.…”
Section: Pembahasanunclassified
“… 10–12 It is indisputable that cardiovascular risk factors (for example, age, duration of type 2 diabetes, smoking, hypertension, hyperglycemia, dyslipidemia, overweight, and obesity) in diabetic patients promote endothelium dysfunction and atherosclerosis of femoral arteries. 7 , 11 Diabetes enhances the risk of inflammation via increases in hs-CRP, interleukin (such as interleukin-4,6,8,17), tumor necrosis factor-alpha, platelet adhesion and aggregation, and coagulation disorders, which contributes to developing endothelium dysfunction. 7 , 13 , 14 Recent studies have demonstrated hypoalbuminemia and an increase in inflammatory factors such as hs-CRP and white blood cell count are the main factors for endothelium dysfunction and atherosclerosis in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%